KEBIJAKAN PUBLIK PEMERINTAH REPUBLIK INDONESIA MENGHADAPI ANGGARAN KHUSUS UNTUK PEMINDAHAN IBU KOTA KE KALIMANTAN TIMUR (Kasus Anggaran Khusus untuk Pemindahan Ibukota Negara dari Jakarta ke Kalimantan Timur) - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
The aim of this research is to know about the budget ofreplacement of the State capital of Jakarta to East Kalimantan Province.The forms of the budget of the organization has thecharacteristics as follow, (1) It is stated in the unity of monitory by thesupporting nonmoneter like production unit or sold unit; (2) To cover thedefined period usually one year; (3) To estimate the potencial profit of thebisness unit; (4) As the commitment; (5) The budget is being reviewed andagreed; (6) After it is being appointed so never change again withou thespecial reason. The location of it is in East Kalimantan in 2016. The methodof the research is qualitative by taking from newspaper, magazine andreports. The data is also taken by observation and interview. The budgethere was falling down until 442 tryllion rupiah. The results are that (1) Thebudget has to be earned from the central government and the companies aswell as the upport from outsider or internatioanal states and the total bugded422 tryllion; (2) The budget is begun from unit the next four years. Thesuggestions are that the government: (1) has to focuse to the budget of theexpense; (2) has to economize the budget during four years working; (3) Toincrease the real income by tax as well as the tourism objects.